Fluorescence nanoscopy with optical sectioning by two-photon induced molecular switching using continuous-wave lasers. - Fölling, J; Belov, V; Riedel, D; Schönle, A; Egner, A; Eggeling, C; Bossi, M; Hell, S (2008)
During the last decade far-field fluorescence microscopy methods have evolved that have resolution far below the wavelength of light. To outperform the limiting role of diffraction, all these methods, in one way or another, switch the ability of a molecule to emit fluorescence. Here we present a novel rhodamine amide that can be photoswitched from a nonfluorescent to a fluorescent state by absorption of one or two photons from a continuous-wave laser beam. This bright marker enables strict control of on/off switching and provides single-molecule localization precision down to 15 nm in the focal plane. Two-photon induced nonlinear photoswitching of this marker with continuous-wave illumination offers optical sectioning with simple laser equipment. Future synthesis of similar compounds holds great promise for cost-effective fluorescence nanoscopy with noninvasive optical sectioning.